Defining a Paradigm Shift - Hickson, Louise (Seminars in Hearing, 2012)
This article is a personal reflection on a paradigm shift from a focus on the technological aspects of hearing health care to a more person-centered approach to rehabilitation. Patient-centeredness and encouraging patients to more effectively self-manage their hearing loss is central to similar changes that have occurred in other areas of health care for people with chronic health conditions. Four sources of evidence for a paradigm shift in rehabilitative audiology are presented in this article: (1) the development and use of programs that extend rehabilitation beyond technology alone, (2) increasing emphasis in the academic audiology literature on patient-centered rehabilitation, (3) changes in the education of audiology students, and (4) the participation and engagement of hearing health care professionals in the work of the Ida Institute to foster greater understanding of the human dynamics of hearing loss.
Keywords: Audiological rehabilitation; aural rehabilitation; hearing impairment; patient centered care